2016
DOI: 10.3390/en9080606
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Analyses on the Rotary Vane Expander Operating Conditions in a Micro Organic Rankine Cycle System

Abstract: Micro (0.5-10 kW) organic Rankine cycle (ORC) power systems are nowadays considered for domestic power generation. Selection of a suitable expander is one of the most important problems connected with the domestic ORC system design. Volumetric machines or micro-turbines can be adopted as an expander in domestic ORC systems. Scroll and screw expanders are a common choice and were successfully applied in different small-and micro-power applications. However, micro-turbines as well as scroll and screw expanders a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…The experimental results showed that the expander indicated work varies in the range of 0.96-4.18 kJ/kg while its internal efficiency varies in the range of 17.2-58.3 % depending on the experimental conditions. The more detailed description of the experiment and experimental results is presented in [3]. The results from the experiment were in a good agreement with the numerical predictions so the model was validated for a given range of temperature and pressure parameters.…”
Section: Description Of the Experimental Test-stand The Multi-vane Ementioning
confidence: 56%
See 2 more Smart Citations
“…The experimental results showed that the expander indicated work varies in the range of 0.96-4.18 kJ/kg while its internal efficiency varies in the range of 17.2-58.3 % depending on the experimental conditions. The more detailed description of the experiment and experimental results is presented in [3]. The results from the experiment were in a good agreement with the numerical predictions so the model was validated for a given range of temperature and pressure parameters.…”
Section: Description Of the Experimental Test-stand The Multi-vane Ementioning
confidence: 56%
“…Presented curves show a standard variation except the strange recompression effect which is visible in the vicinity of φ = 200°. This behaviour stems from the improper construction of the expander and it was described in detail in [3]. This effect is more visible for working fluids with a higher saturation pressure and it results in decrease of efficiency of the expander.…”
Section: Tab 1 Boundary Conditions and Model Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, the ORC systems can offer several benefits to the whole powertrain configuration; at best, power output of the powertrain can be increased by a maximum of approximately 15% depending on the application [26][27][28]. As a consequence of the increased efficiency of the engine, the fuel consumption can be decreased, making the ORC systems desirable for various applications [1,9,29]. Furthermore, a significant advantage of the ORC systems is that they do not depend on the pressure of the exhaust gases, as the only thing that affects the efficiency of the system are the exhaust gas temperature and mass flow rate.…”
Section: Organic Rankine Cycle (Orc)mentioning
confidence: 99%
“…For instance, Kolasiński et al [88] proposed the use of vane and lobe expanders as suitable rotary alternatives to scroll machines in micro-scale applications. With regard to the range of smallscale systems, the twin-screw expander was pointed in the literature as the best candidate [89].…”
Section: Rotarymentioning
confidence: 99%